Digestibility of Dry Matter and Nutrients from Azolla pinnata by Labeo calbasu (Hamilton, 1822) with a Note on Digestive Enzyme Activity - Gangadhar, B.; Umalatha, H.; Hegde, G.; Sridhar, N. (Fishery Technology, 2017)
Digestibility of feed ingredients in the compounded diet is an important factor affecting the growth of fish. A study was conducted in indoor plastic tubs to estimate the in vivo digestibility of dry matter and nutrients by a minor carp Labeo calbasu for a nonconventional feed ingredient – azolla, incorporated at levels ranging from 0-40% using crude fibre as the marker. The activities of major digestive enzymes were also estimated in the gut of fish fed varied levels of azolla. The digestibility values were the highest (p<0.05) at 10% azolla inclusion level. While the total dry matter digestibility and fat digestibility values of control diet were comparable with that of azolla diets up to 30% incorporation, with a decline thereafter; protein and NFE digestibilities were comparable up to 40% incorporation. Activities of majority of digestive enzymes were the highest (p<0.05) at 10% azolla incorporation level showing a decreasing trend at still higher levels. The study reveals the usefulness of azolla for inclusion in calbasu diets. Azolla can be used up to 30% without affecting the digestibility.